Immunomodulator Galectin-9 is Increased in Blood and Skin of Patients with Bullous Pemphigoid - Jasper Pruessmann; Wiebke Pruessmann; Maike M. Holtsche; Beke Linnemann; Christoph M. Hammers; Nina van Beek; Detlef Zillikens; Enno Schmidt; Christian D. Sadik (Medical Journals Sweden, 2021)
Massive recruitment of eosinophils into the dermis is a hallmark of bullous pemphigoid pathogenesis. Identifying the chemoattractant(s) guiding eosinophils into the skin in bullous pemphigoid is a prerequisite to therapeutic targeting of eosinophil recruitment. Galectin -9 is a potent chemoattractant for eosinophils, but its potential role in bullous pemphigoid is unknown. The aim of this study was to determine the expression levels of galectin-9 in serum and skin of patients with bullous pemphigoid. Galectin-9 levels were significantly elevated in serum of patients with bullous pemphigoid compared with age- and sex-matched controls, but did not correlate with disease activity assessed with the Bullous Pemphigoid Disease Area Index. Galectin-9 expression was also increased in lesional skin of patients with bullous pemphigoid, and was expressed predominantly in eosinophils, neutrophils and keratinocytes. In conclusion, these results support the notion that galectin-9 may play a role in the pathogenesis of bullous pemphigoid.